(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj, GdLHYj, GdnqTpgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, J(B966(3g`s
(3ChdgG (B:s
(3GdMeO ddg TQM UOhQfG HdeYI ef TQGFY GdESdGe(B...(3hHYO agPg JYdjbI dWjaI CVaJgG Edi GdeNJUQ GdTQja(B...(3GdehShe HGddeYI GdOeTbjI(B...s
(3BNQgG (B:s
(3haj GdeOI jMda GdefcQ dCUGdI YOe eG jOYjg GdBNQ ef GdRjGOI, Je GdcJGH HYhf Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B3(3,U(B64s
(3GdPQjYI(B:(3L(B11(3,U(B209(3,Qbe(B1757s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis